2019
DOI: 10.1093/mnras/stz2571
|View full text |Cite
|
Sign up to set email alerts
|

Ground-based observation of ZZ Ceti stars and the discovery of four new variables

Abstract: We perform ground based photometric observations of 22 DA white dwarf stars, 10 already known ZZ Cetis and 12 candidates with atmospheric parameters inside the classical instability strip. We report on the discovery of four new variable DA white dwarf stars. Two objects are near the middle of the instability strip, SDSS J082804.63+094956.6 and SDSS J094929.09+101918.8, and two red edge pulsators, GD 195 and L495−82. In addition, we classified four objects as possible variables, since evidence of variability wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
(97 reference statements)
0
16
0
Order By: Relevance
“…Measurements of an anomalous period change can thus be used to estimate the associated axion-electron coupling. From the 250 known variable WDs [145], this has so far only been done for G117-B15A [146][147][148][149][150], R548 [148,151], L19-2 [152], and PG 1351+489 [153]. The reason for this small fraction is that measuring the period change is very difficult: while the periods for the WDs listed here are of the order of a few minutes, their (inherently dimensionless) period changes, Π, are less than about 10 −13 in magnitude.…”
Section: Ubdm Hints: Anomalous White Dwarf Coolingmentioning
confidence: 99%
“…Measurements of an anomalous period change can thus be used to estimate the associated axion-electron coupling. From the 250 known variable WDs [145], this has so far only been done for G117-B15A [146][147][148][149][150], R548 [148,151], L19-2 [152], and PG 1351+489 [153]. The reason for this small fraction is that measuring the period change is very difficult: while the periods for the WDs listed here are of the order of a few minutes, their (inherently dimensionless) period changes, Π, are less than about 10 −13 in magnitude.…”
Section: Ubdm Hints: Anomalous White Dwarf Coolingmentioning
confidence: 99%
“…For the targets with more than one determination for the atmospheric parameters in Table 1, we adopt that obtained from photometry and parallax from Gaia for Figure 1. The sample of ZZ Ceti stars known to date is depicted in this figure, and was extracted from the works of Bognar & Sodor (2016); Hermes et al (2017a); Su et al (2017); Romero et al (2019b); Vincent et al (2020). The values for effective temperature and surface gravity derived from spectroscopy were corrected by 3D convection (Tremblay et al 2013) for all objects (Córsico et al 2019).…”
Section: New Zz Ceti Starsmentioning
confidence: 99%
“…Each pulsation mode propagates in a specific region providing information on that particular zone, where its amplitude is maximum (Tassoul et al 1990). Thus, we can perform an asteroseismic study, where we compare the observed periods with the theoretical period spectrum, computed using representative models, to uncover the inner stellar structure (see e. g. Romero et al 2012Romero et al , 2019.…”
Section: Introductionmentioning
confidence: 99%